Fracture behavior of sandstone with partial filling flaw under mixed-mode loading: Three-point bending tests and discrete element method - Dongdong Ma; Yu Wu; Xiao Ma; Xunjian Hu; Wenbao Dong; Decheng Li; Lingyu Li (Journal of Rock Mechanics and Geotechnical Engineering)
The fracture behavior of natural fracture in the geological reservoir subjected to filling property, affects the crack initiation and propagation under stress perturbation. Partial filling flaws were intermediate between open fractures and filled fractures, the fracture response may be worth exploring. In this work, the effect of the filling property of sandstone with partial filling flaws on the fracture behavior was systematically investigated based on three-point bending tests and the numerical approach of discrete element method (DEM). In the laboratory, semi-circular three-point bending tests were carried out with partial filling flaws of various filling strengths. Based on this, numerical simulations were used to further investigate the effect of the filling ratio and the inclination of the partial filling flaw on the mechanical and fracture responses, and the effect of the partial filling flaw under mixed-mode loading on the fracture mechanism was elucidated coupled with acoustic emission (AE) characteristics. The obtained results showed that the increase in filling strength and filling ratio of partial filling flaw led to an increase in peak strength, with a decreasing trend in peak strength with the inclination of partial filling flaw. In terms of crack propagation pattern, the increasing filling strength of the partial filling flaw induced the transformation of the fracture mechanism toward deflection, with a tortuosity path, while the filling ratio and inclination of partial filling flaw led to fracture mechanism change from deflection to penetration and attraction, accompanied with a larger AE event source in filler. Accordingly, the b-value based on the Gutenberg-Richter equation fluctuated between 5 and 4 at low filling ratio and inclination and remained around 5 at high filling ratio and inclination of partial filling flaw. Related results may provide an application prospective for reservoir stimulation using the natural fracture system.